Liquid-Phase Polymer-Based Retention: Theory, Modeling, and Application for the Removal of Pollutant Inorganic Ions - Manuel Palencia (Journal of Chemistry)
The aim of this work is to give the theoretical background of liquid-phase polymer-based retention (LPR) technique, provide a complete model of separation process, and evaluate its application for the removal of pollutant inorganic ions (PIIs) from aqueous solution. Thus, fundaments of LPR modeling by washing method from the ion distribution in active and passive zones are specified and its application was evaluated for cadmium removal using poly(sodium styrene sulfonate) as water-soluble polymer (WSP). LPR simulations were performed using a semiempirical description from data of concentration, filtration factorm, and retention coefficients. It is concluded that semiempirical simulation of PII retention by WSP can be performed from a small amount of experimental data using the described modeling. In addition, new approximations associated with molecular structure of polymer should be performed and linked to parameters of LPR experiments.